What fire brings : a thriller - Hall, Rachel Howzell (Thomas & Mercer, 2024)
"Bailey Meadows has just moved into the remote Topanga Canyon home of thriller author Jack Beckham. As his writer-in-residence, she's supposed to help him once again reach the bestseller list. But she's not there to write a thriller--she's there to find Sam Morris, a community leader dedicated to finding missing people, who has disappeared in the canyon surrounding Beckham's property. The missing woman was last seen in the drought-stricken forest known for wildfires and mountain lions. Each new day, Bailey learns just how dangerous these canyons are--for the other women who have also gone missing here...and for her. Could these missing women be linked to strange events that occurred decades ago at the Beckham estate? As fire season in the canyons approaches, Bailey must race to unravel the truth from fiction before she becomes the next woman lost in the forest"--